Acute ischemic colitis with hematochezia related to baloxavir marboxil treatment for influenza A. Issue 12 (December 2019) - Kanai, Norihito; Hashimoto, Takafumi; Fukuda, Masataka; Shijyo, Takayuki
Abstract: Oseltamivir, an established oral anti-influenza medication, increases the risk of ischemic colitis. Baloxavir marboxil is a novel oral anti-influenza medication, and few studies have evaluated its potential side effects, including ischemic colitis. Moreover, as influenza A can also induce ischemic colitis, drug-induced colitis associated with anti-influenza medication is not clearly understood. In this report, we describe the case of a 62-year-old Japanese woman who developed acute ischemic colitis after taking baloxavir for influenza A. The day after taking baloxavir (day 2), the patient experienced abdominal pain, diarrhea, and nausea. On day 3, she had developed hematochezia and decided to visit our hospital. Upon presentation, inflammation of the descending and sigmoid colon was detected by abdominal echography and computed tomography. Fluid replacement therapy and dietary restrictions were initiated. On day 4, the inflammation of the descending colon and marked intestinal edema were confirmed by colonoscopy. She was clinically diagnosed with ischemic colitis, from which she recovered completely by day 9. This case suggests that patients taking baloxavir may be at risk of developing ischemic colitis with hematochezia and underscores the need to further study the induction of this condition by commonly used oral anti-influenza agents.